2000
DOI: 10.1159/000007828
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Angiosarcoma of the Liver Preoperatively Presenting as Giant Hemangioma

Abstract: Background: Hepatic angiosarcomas are rare tumors most often associated with exposure to vinyl chloride or other carcinogens. Only a few cases have been published without such a history. Case Report: We report the case of a 73-year-old woman who was admitted to our medical department with unclear upper abdominal pain, thrombocytopenia and anemia. Both computed tomography and magnet resonance imaging revealed a giant hemangioma in the right liver with multiple small hemangiomas. To cure the problem of thrombocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In the few published reports on this topic, attention is mostly on the false diagnosis of malignancy in patients with a benign lesion [16]. In 1992, Shimizu et al [10] reported on 32 patients with benign lesions who were operated on with a false diagnosis of cancer; HA was the most frequent final diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the few published reports on this topic, attention is mostly on the false diagnosis of malignancy in patients with a benign lesion [16]. In 1992, Shimizu et al [10] reported on 32 patients with benign lesions who were operated on with a false diagnosis of cancer; HA was the most frequent final diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently the use of procaine as treatment option for pain relief in AP was recommended by the German consensus conferences on management of acute and chronic pancreatitis [3, 4, 5]. The rationale for the use of procaine is its local analgesic effect and its inhibitory effect on phospholipase A 2 catalytic activity, which is a critical enzyme in the pathogenesis of AP [11, 12]. However, there are no prospective trials proving any beneficial effect of intravenously administered procaine on pain in patients with AP.…”
Section: Introductionmentioning
confidence: 99%